Factors Affecting Economic Growth in West Sumatera Province Using Panel Data Regression Analysis - Helma; Sherly Helma Putri (Mathematical Journal of Modelling and Forecasting, 2023)
Economic development is considered successful if the economic growth rate of its people reaches a high level. Indonesia has positive economic growth with economic growth rates above 5% in each quarter. However, the high economic growth of Indonesia does not mean that all regions have the same growth rate. Where the increase in the number of goods and services received or the added value of production factors is often referred to as economic growth. Regional economic growth in West Sumatera Province is known to tend to be negative. This study aims to obtain an overview of panel data regression models and factors that have an influence on economic growth in West Sumatera Province for the period 2018 to 2022. The best regression model obtained is the fixed effect model (FEM), where at a significant level of 5%, the factors that have an influence and positive relationship on economic growth are the human development index and government spending.